2017
DOI: 10.22201/cgeo.20072902e.2017.3.540
|View full text |Cite
|
Sign up to set email alerts
|

Geoquímica y mineralogía de los jales del distrito minero Tlalpujahua-El Oro, México, y sus implicaciones de impacto ambiental

Abstract: RESUMENLos depósitos de jales del distrito minero de Tlalpujahua y El Oro (DIMITO) fueron apilados sobre laderas y cañadas con un sistema de drenaje activo y cubriendo un basamento constituido por calizas carbonosas y lutitas ± andesitas que constituyen la roca encajonante de las vetas auríferas de tipo epitermal. Su morfología actual muestra profundos canales y cárcavas de erosión y se ha estimado una pérdida de material >27-34 % de su volumen original. Se presentan los resultados de un estudio cartográfico d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…Mining is one of Mexico's most traditional economic activities, practiced since pre-Hispanic times [1], and it is a regional expansion source since colonization. It has been present in the country's development as an essential modernization and development factor, providing goods to virtually all industries, including construction, metallurgical, steel, chemistry, and electronics.…”
Section: Introductionmentioning
confidence: 99%
“…Mining is one of Mexico's most traditional economic activities, practiced since pre-Hispanic times [1], and it is a regional expansion source since colonization. It has been present in the country's development as an essential modernization and development factor, providing goods to virtually all industries, including construction, metallurgical, steel, chemistry, and electronics.…”
Section: Introductionmentioning
confidence: 99%
“…In Mexico, some states with important mining activity such as Zacatecas, San Luis Potosí, Guerrero and Sonora have been affected by the pollution by heavy metals (Hg, Ar, Pb and Cr) attributed to the mining industry and effected by the inadequate management of solid mining wastes (Covarrubias and Peña Cabriales, 2017;Corona-Chávez et al, 2017). On the other hand, INEGI (2013) reported that the surface water or shallow groundwater represents the main source of domestic water supply for a large number of rural populations and many cities in Mexico.…”
Section: Introductionmentioning
confidence: 99%